Functional magnetic resonance imaging following epimacular and internal limiting membrane peeling - ipsilateral and contralateral findings - Lešták, Ján; Kalvodová, Bohdana; Karel, Ivan; Tintěra, Jaroslav (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
PURPOSE: The purpose of this study was to find out whether peeling of the epimacular membrane (EMM) and internal limiting membrane (ILM) for symptomatic lamellar macular hole (LMH), causes impairment of the visual cortex. PATIENTS AND METHODS: This pilot study consisted of 8 eyes of 4 patients (2 females and 2 males), mean age 69.25 years (60-83 years), who underwent pars plana vitrectomy and EMM and ILM peeling in one eye for lamellar macular hole The second eye remained intact. The patients had no other ophthalmological or neurological disease. The control group consisted of 20 eyes of 10 healthy people (8 females and 2 males). mean age 52 years (34-65 years). In all of them, we performed functional magnetic resonance imaging (fMRI) of the brain to the visual paradigm (black and white chessboard of 25.8 x 16.2 degrees in size), as well as in patients 3-4 years following the surgery. For statistical processing, we used ANOVA and multiple regression for adjustment for the age of patients. RESULTS: In all patients, we recorded a decrease in fMRI activity of the brain following stimulation of the eye in which surgical intervention was performed. The fMRI values using ANOVA (without adjustment for age) were significantly different between groups (P<0.001). Following adjustment for age and the use of multiple regression, the fMRI values in the operated eyes were lower by 4142.39 vs the control eyes. In the group of unoperated eyes, the fMRI values were lower by 2807.39 vs the control eyes. Therefore, the results did not differ very much from the results without adjustment. CONCLUSION: In patients with symptomatic partial macular defect following EMM and ILM peeling, we recorded a significant decrease of the fMRI activity of the brain following stimulation of the operated eye, compared to the control group. We also found a decrease in activity in fMRI following stimulation of the contralateral eye. These findings lead us to the conclusion that EMM and ILM peeling may cause secondary impairment of the visual centres in the brain, not only on the side of the surgical intervention, but also on the contralateral side.
Keywords: dospělí; Epiretinal Membrane; Magnetic Resonance Imaging; Female; Adult; výsledek terapie; ženské pohlaví; Retinal Perforations; lidé; vitrektomie; Pilot Projects; magnetická rezonanční tomografie; pilotní projekty; Treatment Outcome; Vitrectomy; epiretinální membrána; Male; Aged; lidé středního věku; senioři; mužské pohlaví; zraková ostrost; Visual Acuity; Middle Aged; perforace sítnice; Humans